Autoethnographic engagement in participatory action research: Bearing witness to developmental transformations for college student activists. Issue 1 (March 2023) - Vang, MaiNeng; Wolfgram, Matthew; Smolarek, Bailey; Lee, Lena; Moua, Payeng; Thao, Ariana; Xiong, Odyssey; Xiong, Pa Kou; Xiong, Ying; Yang, Lisa
This article documents and analyzes autoethnographic engagement in participatory action research (PAR)—a reflective, irritative, and dialogic writing and team-discussion process which documents researcher-activist experiences and contextualizes them within the action research process. We document autoethnography as implemented in a research partnership between HMoob American college student activists and education researchers, to study the systems of oppression and inform advocacy to support HMoob American students at a predominantly white university. Autoethnography informs all aspects of the PAR project, from the development of research questions, to data collection, analysis, and writing, to the implementation of plans for action. We provide evidence from selections of the team's autoethnographic journals, of the role of autoethnographic engagement as a PAR research technique that can facilitate and bear witness to the developmental transformations for emerging PAR activists—specifically, the cultivation of critical consciousness, the critical re-framing of issues of cultural-community identity, and the formation of an identity as a researcher-activist. We argue that autoethnography provides a practical technique for PAR teams for engaging in iterative cycles of critical self-reflective praxis (Freire, 2011), facilitating the development of critically-engaged researchers and the formation of analyses that are epistemologically grounded and action-oriented, addressing issues of power asymmetries within research.